Pediatric Surgical Research Output in Germany in the Last 30 Years – An Assessment and International Comparison of Three Dedicated Paediatric Surgical Journals - Oetzmann von Sochaczewski, Christina; Muensterer, Oliver J. (Frontiers in Pediatrics, 2020)
Purpose: Research output of once-leading countries in surgical journals is decreasing despite an overall increase of scientific publications by 8% per year. We aimed to assess research outputs of German, Dutch, and Israeli paediatric surgeons in dedicated paediatric surgical journals in order to get insight into trends in paediatric surgical research. Methods: We collected bibliographic information on all original articles in the Journal of Pediatric Surgery, European Journal of Pediatric Surgery, and Pediatric Surgery International in 1985-1988, 2000-2003, and 2015-2018 that had a German, Dutch or Israeli last author from a department of paediatric surgery. Citation counts were obtained from the Web of Science. Results: Research output of German paediatric surgery decreased from 19 manuscripts in 1988 (0.1/surgeon/year) to 8 manuscripts in 2017 (0.02/surgeon/year), whereas those of the Netherlands increased from 2 manuscripts in 1985 (0.08/surgeon/year) to 12 manuscripts in 2016 (0.3/surgeon/year). The declining German research output negatively correlated with increasing numbers of specialist paediatric surgeons for total (τ=-0.54; P=0.0156) and manuscripts per surgeon (τ=-0.79; P=0.0001), resulting in a negative trend over time (χ²=11.845, P=0.0006). Analyses of citation patterns revealed that manuscripts by Dutch paediatric surgeons and those published in the Journal of Pediatric Surgery had higher absolute citation counts than the reference category of a German manuscript in the European Journal of Pediatric Surgery. Age-corrected citation rates resembled this result by increasing from 2000-2003 (x̃=0.799, range: 0-3.368) to 2015-2018 (x̃=2, range: 0-5) (P=0.035) for the Netherlands. Assessment of manuscript types revealed that the proportion of prospective studies increased in the German sample (χ²=5.05, P=0.0246), but remained the lowest among the comparators. Surprisingly, the proportion of non-clinical manuscripts from Germany also increased over time (χ²=4.001, P=0.0455), whereas it remained constant in both the Netherlands and Israel. Conclusion: German paediatric surgical research output decreased in the last thirty years based on the sample of dedicated paediatric surgical journals, while Dutch productivity increased. Citation rates – as a measure of scientific impact – were associated and increased with Dutch manuscripts. The involved factors remain to be determined and whether this represents a shift towards other journals or mirrors a general development.